Effect of Parent’s International Migration on the Educational Performances of Left-Behind Children in Morocco - El Alaoui, Aicha; Ahbala, Salah (European Scientific Journal, ESJ, 2024)
This paper focuses on examining the effects of parent’s international migration on the educational outcomes of left-behind children. This, however, is with special emphasis on how family environment and school characteristics affects the educational achievements of left-behind children. A sample was selected from the survey conducted in Fkih Ben Salah, a small town in Morocco, within the Béni Mellal-Khénifra region. This survey, administered in 2020, included 407 children from 16 primary schools. The results of the propensity score matching method showed that the international migration of parents had a significant effect on the school performance of their left-behind children. Furthermore, the Oaxaca-Blinder decomposition analysis showed that 36.34% of the differences in the children’s school performance during the first semester of the year 2020 can be explained by factors such as student–teacher ratio, class size, and socio-economic index of class, accounting for 12.82%, 38.47%, and 31.35%, respectively. The empirical findings also revealed that left-behind children are at risk of social exclusion, especially in public schools. Targeted interventions should be adopted to improve the educational outcomes of left-behind children. In addition, these interventions should assist immigrant parents in facilitating their children’s first journey and enhancing the student-teacher ratio.